2012
DOI: 10.1370/afm.1394
|View full text |Cite
|
Sign up to set email alerts
|

A Family Medicine Residency Program Curriculum Resource

Abstract: Family medicine has been thrust into the national spotlight by the Affordable Care Act of 2010 bringing the concept of the medical home to the forefront and placing family physicians at the hub of the medical care delivery model of the future. These events also task training programs across this country with the burden of producing the right product to meet the demands of what our health system needs: competent, well rounded family physicians. How can we insure quality of our graduates and consistency of our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our study suggested that it was difficult for GPs to make suitable arrangements between work and training, and the distant education via networks was a feasible training method during training. By creating a web-based resource for trainees to use, a consistent framework for trainees can be provided to guide their learning and develop competence in the broad scope of the practice [22] . A study [23] in Fujian province verified and supported our view that the contradiction between work and training can be settled down by on-line training for general practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that it was difficult for GPs to make suitable arrangements between work and training, and the distant education via networks was a feasible training method during training. By creating a web-based resource for trainees to use, a consistent framework for trainees can be provided to guide their learning and develop competence in the broad scope of the practice [22] . A study [23] in Fujian province verified and supported our view that the contradiction between work and training can be settled down by on-line training for general practitioners.…”
Section: Discussionmentioning
confidence: 99%